2013
DOI: 10.1096/fj.13-232900
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mesenchymal stem cell fate by pigment epithelium‐derived factor (PEDF) results in increased adiposity and reduced bone mineral content

Abstract: Pigment epithelium-derived factor (PEDF), the protein product of the SERPINF1 gene, has been linked to distinct diseases involving adipose or bone tissue, the metabolic syndrome, and osteogenesis imperfecta (OI) type VI. Since mesenchymal stem cell (MSC) differentiation into adipocytes vs. osteoblasts can be regulated by specific factors, PEDF-directed dependency of murine and human MSCs was assessed. PEDF inhibited adipogenesis and promoted osteoblast differentiation of murine MSCs, osteoblast precursors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 47 publications
3
62
2
Order By: Relevance
“…This finding contrasted an earlier study that showed that PEDF is synthesised by adipose tissue and is downregulated during differentiation to mature adipocytes (Kratchmarova et al, 2002). PEDF can block mesenchymal stem cell (MSC) differentiation to adipocytes in order to facilitate differentiation to osteoblasts (Gattu et al, 2013). In PEDF −/− mice, total body adiposity was increased by >50% compared with controls, illustrating its systemic role as a negative regulator of adipogenesis.…”
Section: Elevated In Metabolic Disorderscontrasting
confidence: 92%
“…This finding contrasted an earlier study that showed that PEDF is synthesised by adipose tissue and is downregulated during differentiation to mature adipocytes (Kratchmarova et al, 2002). PEDF can block mesenchymal stem cell (MSC) differentiation to adipocytes in order to facilitate differentiation to osteoblasts (Gattu et al, 2013). In PEDF −/− mice, total body adiposity was increased by >50% compared with controls, illustrating its systemic role as a negative regulator of adipogenesis.…”
Section: Elevated In Metabolic Disorderscontrasting
confidence: 92%
“…Mechanisms by which PEDF regulates bone mineralization remain undefined. We and others showed that PEDF increased MSCs-osteoblastic mineralization; in addition, we showed that PEDF enhanced expression of genes that encode proteins which promote matrix mineralization [11,12]. In this report, we examined whether VEGF which plays important role in bone development is also regulated by PEDF.…”
Section: Discussionmentioning
confidence: 94%
“…The major bone defect in these patients is presence of excessive osteoid build up that fails to mineralize [710]. We and others have shown that PEDF promotes mesenchymal stem cell differentiation and increases osteoblast mineralization [11,12]. In addition, we reported that PEDF reduced expression of sclerostin by osteocytes [13].…”
Section: Introductionmentioning
confidence: 99%
“…The lineage commitment of mesenchymal stem cells is controlled by different groups of protein such as bone morphogenic protein family (BMP), hedgehog protein family, nuclear hormone super family, wingless protein family, etc. (Busser et al, 2013;Gattu et al, 2013). The role of each transcription factor is explained in detail in the following sections.…”
Section: Origin Of White and Brown Adipocytesmentioning
confidence: 99%